LGG-24. TEMPORAL GENOMIC HETEROGENEITY IN PEDIATRIC LOW-GRADE GLIOMAS. Issue 2 (22nd June 2018) - Fuller, Christine; Schafer, Austin; Boue, Daniel; Osorio, Diana; Finlay, Jonathan; Rush, Sarah; Wright, Erin; Hoffman, Lindsey; Yanez-Escorza, Nancy; Reuss, Jamie; Hummel, Trent; Salloum, Ralph; et al.
Abstract: INTRODUCTION: Pediatric low-grade gliomas (pLGG) represent the most common brain tumors in children. Though malignant transformation is rare, these tumors pose a formidable therapeutic challenge due to anatomy-limiting surgical options and local recurrence. The temporal and therapy-driven genomic evolution in pLGG is largely unknown. METHODS: To characterize the temporal genomic heterogeneity of pLGG, we performed fluorescence in situ hybridization, mutation-specific immunohistochemistry, and exome analyses on paired tumor samples from primary diagnostic and subsequent surgeries of 27 pLGG patients. RESULTS: 59 tumor samples were available for review and included pilocytic / pilomyxoid astrocytoma (PA) (67%), low grade astrocytoma (19%), ganglioglioma (11%), and pleomorphic xanthoastrocytoma (3%). BRAF duplication/rearrangement was detected in 56% of tested samples, limited to PA in all but one patient (ganglioglioma). 58% of samples harbored CDKN2A deletion, which was demonstrable across various histologies. BRAF duplication/rearrangement was found consistently conserved across primary and subsequent surgical samples, whereas CDKN2A status changed in 60% of tested temporal pairs, with deletion acquisition the most frequent finding (40%) at second surgery. Likewise, BRAF V600E mutation in one PA was lost at second surgery. Although CDKN2A status changes were seen following surgery alone, the addition of chemo-and/or radiation therapy was associated with a higher rate of temporal CDKN2A deletion acquisition (50%, versus 33% with surgery alone). CONCLUSION: Temporal genomic heterogeneity may be encountered in a significant proportion of pLGG, with some alterations potentially facilitated by therapy. Recurrence biopsy may provide improved guidance, particularly if targeted therapeutics are being considered.